2011
DOI: 10.4103/2229-4708.90356
|View full text |Cite
|
Sign up to set email alerts
|

The RP-HPLC method for simultaneous estimation of esomeprazole and naproxen in binary combination

Abstract: Objective:A simple, precise, reliable, rapid, sensitive and validated RP-HPLC method has been developed to determine esomeprazole magnesium trihydrate (ESO) and naproxen (NAP) in synthetic mixture form.Materials and Methods:Chromatographic separation achieved isocratically on Phenomenex, Luna C18 column (5 μm, 150mm × 4.60mm) and acetonitrile: phosphate buffer (pH 7.0) in the ratio of 50:50 (v/v) as the mobile phase, at a flow rate of 0.5 ml/min. Detection was carried out at 300 nm. The retention times for NAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…The EPM component is indicated to decrease the risk of developing NPX associated gastric ulcers 9 . The literature data revealed that there are simultaneous estimation methods developed for NPX and EPM in combined dosage form for assay and related substances using high performance liquid chromatography [10][11][12][13][14] and using ultraviolet spectroscopy [15][16][17][18][19] . No methods were established for content uniformity test.…”
Section: Introductionmentioning
confidence: 99%
“…The EPM component is indicated to decrease the risk of developing NPX associated gastric ulcers 9 . The literature data revealed that there are simultaneous estimation methods developed for NPX and EPM in combined dosage form for assay and related substances using high performance liquid chromatography [10][11][12][13][14] and using ultraviolet spectroscopy [15][16][17][18][19] . No methods were established for content uniformity test.…”
Section: Introductionmentioning
confidence: 99%
“…RP-HPLC and UV methods have been widely used for estimation of drug in bulk and dosage forms (Prasanthi et al 2011;Shukla et al 2011;Basaveswara Rao et al 2012;Singh et al 2012;Banerjee and Vasava, 2013;Singh and Dahiya, 2014). Literature review also revealed that simultaneous analysis of naproxen and esomeprazole has been carried out by UVSpectrophotometer (Mahaparale et al 2013;Patel et al 2012;, RP-HPLC (Jain et al 2011;Deshpande et al 2014;Ampati et al 2014;Saravanan et al 2014;Razzaq et al 2012), stability indicating simultaneous estimation of naproxen and esomeprazole by RP-HPLC (Reddy et al 2011), LC-MS/MS (Gopinath et al 2013) and UPLC method (Rao et al 2013;Bhavyasri et al 2013). The present work describes simple, specific, rapid, accurate and precise chromatographic method based on RP-HPLC mechanism for estimation of drugs in tablet dosage form.…”
Section: Introductionmentioning
confidence: 99%
“…Also, as per literature there are many methods used to validate of tadalafil alone or in combined with other drugs in drug formulation, plasma and other fluids; HPLC (Farthing et al, 2010;Kamepalli Sujana et al, 2012;Rajpar et al, 2012;Nagaraju et al, 2012;Samala et al, 2013). Many methods indicated that HPLC was a consistent way for the evaluation of esomeprazole and tadalafil separately in several samples, such as pharmaceutical formulations, drinks, plasma and other biological fluids, and it can be used to study the pharmacokinetics parameters of these drugs (Onal and Oztunç, 2006;Farthing ;Dilip et al, 2011;Kumar et al, 2011;Jain et al, 2011;Nalwade et al, 2012;Kamepalli Sujana et al, 2012;Rajpar et al, 2012;Nagaraju et al, 2012;Samala et al, 2013). Up to date literature survey indicate no method for simultaneous estimation of both esomeprazole and tadalafil in pharmaceutical formulation.…”
Section: Tadalafilmentioning
confidence: 99%
“…Several methods for validation and measurement of esomeprazole alone or in combination with other drugs were used in different drug formulations, plasma and other fluids such as; HPLC (Onal and Oztunç, 2006;Dilip et al, 2011;Kumar et al, 2011;Jain et al, 2011;Nalwade et al, 2012), UVSpectrophotometery (Patil Shamkant et al, 2009) and LC-MS/MS (Hultman et al, 2007). Also, as per literature there are many methods used to validate of tadalafil alone or in combined with other drugs in drug formulation, plasma and other fluids; HPLC (Farthing et al, 2010;Kamepalli Sujana et al, 2012;Rajpar et al, 2012;Nagaraju et al, 2012;Samala et al, 2013).…”
Section: Tadalafilmentioning
confidence: 99%